Predictors of emergency abdominal surgery postoperative recovery in Hai Duong, Viet Nam - Du, Phung Van; Duangpaeng, Supaporn; Masingboon, Khemaradee (วารสารวิจัยทางวิทยาศาสตร์สุขภาพ วิทยาลัยพยาบาลบรมราชชนนี จังหวัดนนทบุรี, 2017)
Abstract Emergency Abdominal Surgery (EAS) is performed under critical life-threatening conditions that require operation as soon as possible. In such cases, the preparation of the patient for surgery may be less than optimal. The risk of post-surgical complications in EAS patients is high and, as a result, postoperative recovery in this group can be longer and poorer. The purpose of this predictive correlation study was to examine the effects of postoperative complications, comorbidity, social support, and perceived postoperative nursing care on postoperative recovery among EAS patients in Vietnam. Simple random sampling was used to recruit 92 patients who had undergone EAS. Research instruments were a Personal Demographic and a Health Information Record, the Charlson Comorbidity Index, the postoperative quality of recovery, the social support questionnaire, and the short form of the caring behavior inventory. Data analysis consisted of descriptive statistics and multiple regression analysis. Results revealed that mean score of total postoperative recovery was 95.69 (SD = 11.05) of a possible 150. Postoperative complications, comorbidity, social support, and perceived postoperative nursing care accounted for 56.2 % of the variation in postoperative recovery (R2 = .56, F(4, 87) = 27.95, p<.001). The strongest predictor of postoperative recovery among EAS patients was postoperative complications (β = -.41, p <.001). The findings suggest that nurses should take a holistic approach, including focusing on comorbidity awareness and treatment, preventing postoperative complications, providing social support, and improving perceived postoperative nursing care. This should enhance postoperative recovery among emergency abdominal surgery patients. Further research should focus on the efficacy of these and other nursing interventions.